On the issues and challenges of Fiber-Wireless (Fi-Wi) networks - Win, Harry Tin; Pathan, Al-Sakib Khan (Hindawi Publishing Corporation, 2013)
The objective of this article is to present various aspects of Fiber-Wireless (Fi-Wi) networks, which is a technology of current interest of the researchers. Fiber-wireless technology, known in short as “Fi-Wi,” is a combination of optical-fiber-based network and wireless network. Fi-Wi has recently come forward as one of the emerging future network technologies yet the term is often mixed up with wireless-fidelity (Wi-Fi) technology. In fact, Wi-Fi network could be included in a Fi-Wi architecture. Due to the unfamiliarity with the term, “Fi-Wi” and similar sounding commonly known “Wi-Fi,” many students, even academics and practitioners sometimes may not be able to differentiate between these. In the recent years, a good number of works on various issues of Fi-Wi have come out, but an overall survey with the latest advancements in the area is yet to be found. Hence, in this work, we analyze various issues and challenges of implementing Fi-Wi networks in practical scenarios to allow researchers to find future directions of research and general readers to understand the issues better.